Pengaruh Perbaikan Pelayanan Perpustakaan Dalam Peningkatan Minat Baca Siswa-Siswi Di SMP Kartini Taman - Astrid Eka Wahyu Cahya Megananda; Rizkya Dwijayanti (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
Libraries play an important role in determining how the academic climate in schools is formed. To maximize scientific activities, the library is organized as a hierarchical system with many purposes and functions. The main reason why the goals and functions of libraries cannot be implemented effectively is because most of the school libraries in Indonesia currently do not meet the demands, both in terms of convenience and selection of library materials. Therefore, steps must be taken to restore proper library operations. The impact of better library services on the reading interest of SMP Kartini Taman students was one of the topics raised. This project is just one of many that Kampus Merdeka is undertaking as part of the Teaching Campus initiative. The service period in 2023 lasts from February 20 to June 16. Serving at the Junior High School which is located on Jl. Ki Suryo Jati Utara, Kedungturi Village, Taman District, Sidoarjo Regency, is the responsibility of our team. Through the implementation of school library management reform initiatives, this program seeks to restore the function of the school library in accordance with its vision and mission. The planning stage (Planning), the organizing stage (Organizing), the implementation stage (Actuating), and the control stage are the first steps in improving the administrative services of the implemented school library. Collecting data in this service is carried out using a qualitative descriptive methodology which includes interviews, observations, and documentation studies. Based on the initiatives made and the findings, the children's enthusiasm for reading in class increased. Thus, efforts to improve library services are ensured to be successful and right on target.